PENGARUH TERPAAN VIDEO TIKTOK SPG GOOD PONSEL DALAM MENINGKATKAN BRAND AWARENESS GOOD PONSEL PADA REMAJA DI KOTA DENPASAR - Darmawan, Deri; Amanda Gelgel, Ni Made Ras; Pradipta, Ade Devia (E-Jurnal Medium, 2021)
Tiktok became the most downloaded non-game category application worldwide as of September 2020. TikTok Good Ponsel account is now one that is quite popular. This study aims to determine the effect of the TikTok Sales Promotion Girls Good Ponsel video in increasing the brand awareness of Good Ponsel to teenagers in Denpasar. The theory used in this research is Stimulus Organism Response Theory. This type of research used quantitative associative. The findings in this study were it has a positive and significant effect. Denpasar City youth can easily recognize Good Ponsel because the TikTok Sales Promotion Girls Good Ponsel videos without assistance (advertising/promotion) and Sales Promotion Girls have succeeded in attracting the attention of teenagers as evidenced by the highest average score on the brand awareness variable. This is sufficient to indicate that Good Ponsel has formed brand awareness for teenagers in Denpasar City. Keywords: Brand awareness, Good Ponsel, Sales Promotion Girls